Performance of Tetranychus urticae and Neoseiulus californicus on strawberry cultivars and assessment of the effect of glandular trichomes - Gugole Ottaviano, María Fernanda (2013)
Fil: Gugole Ottaviano, María Fernanda. Centro de Estudios en Parasitología y Vectores (CEPAVE). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina